2010
DOI: 10.1213/ane.0b013e3181cb3ebf
|View full text |Cite
|
Sign up to set email alerts
|

Resistive-Heating or Forced-Air Warming for the Prevention of Redistribution Hypothermia

Abstract: Prewarming should be considered part of the anesthetic management when patients are at risk for postoperative hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1
24

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 19 publications
6
48
1
24
Order By: Relevance
“…Redistribution of body heat from the core to the periphery was unusually small in this study and similar In most clinical studies, the redistribution of heat after the induction of anaesthesia leads to a reduction in core temperature of about 0.3°C to 0.8°C [9][10][11][12] in the first hour, whereas under experimental conditions it can reach up to 1.7°C [13]. This small decrease in core temperature may be explained by the fact that patients were kept comfortably warm during the entire preoperative period (i.e., from the ward, during transport to the operating theatre and at the induction of anaesthesia) with the same effective insulating hospital blanket as was used during the operation.…”
Section: Discussionsupporting
confidence: 81%
“…Redistribution of body heat from the core to the periphery was unusually small in this study and similar In most clinical studies, the redistribution of heat after the induction of anaesthesia leads to a reduction in core temperature of about 0.3°C to 0.8°C [9][10][11][12] in the first hour, whereas under experimental conditions it can reach up to 1.7°C [13]. This small decrease in core temperature may be explained by the fact that patients were kept comfortably warm during the entire preoperative period (i.e., from the ward, during transport to the operating theatre and at the induction of anaesthesia) with the same effective insulating hospital blanket as was used during the operation.…”
Section: Discussionsupporting
confidence: 81%
“…peri-operative core temperatures between patients pre-warmed through resistive heating [102] but not forced-air warming when compared with controls [103,104]. Furthermore, an earlier study assessing the clinical impact of extending peri-operative conductive warming during abdominal surgery has also shown that the mattresses are well tolerated and that pre-and postoperative conductive warming significantly reduces blood loss and complication rates [105].…”
Section: Resistive Heatingmentioning
confidence: 99%
“…De Witte JL ve ark. (8) çalışmasında, hastaların forced-air veya rezistif ısıt-ma yöntemlerinden herhangi biriyle preoperatif ısıtıl-masının postoperatif komplikasyon sıklığını azalttığı Postop enfeksiyon n,% Hemodinamik instabilite n,% Solunum sıkıntısı n,% Kardiyak morbidite n,% Ortalama kan kaybı Ort±SS (medyan) Hastanede kalış süresi Ort±SS (medyan)…”
Section: Discussionunclassified
“…Hastaların preoperatif ısıtılması gerektiği ve preoperatif dönemde ısıtmanın anestezi yönetiminin bir parçası olduğu De Witte JL ve ark. (8) tarafından önemle vurgulanmıştır. Çalışmamızda da hastalar preoperatif dönemde 30 dk.…”
Section: Discussionunclassified